Prinsip Keadilan Restoratif dalam Penghentian Penuntutan Melalui Kompensasi dan Restitusi pada Tindak Pidana Pencurian - Andry Andani; Ilham Kurniawan Dartias; Tri Dede Darmawan (Universitas Batanghari Jambi, 2026)
The implementation of restorative justice principles in Indonesia's criminal justice system represents a significant legal reform aimed at resolving criminal cases through the restoration of victims' rights, the accountability of offenders, and the achievement of balanced justice within society. This study aims to analyze the regulation of termination of prosecution based on restorative justice through compensation and restitution mechanisms in theft cases and its implications for the reform of Indonesia's criminal law system. This research employs a normative legal research method using statutory and conceptual approaches. The legal materials consist of primary, secondary, and tertiary legal sources, which are analyzed qualitatively through library research. The findings indicate that the legal framework governing the termination of prosecution based on restorative justice is established under Law Number 1 of 2023 concerning the Criminal Code, Law Number 20 of 2025 concerning the Criminal Procedure Code, Attorney General Regulation Number 15 of 2020, National Police Regulation Number 8 of 2021, and Law Number 13 of 2006 as amended by Law Number 31 of 2014 concerning the Protection of Witnesses and Victims. Nevertheless, the relationship between termination of prosecution and the implementation of compensation and restitution has not yet been comprehensively regulated. Therefore, harmonization of the relevant legal provisions is necessary to ensure legal certainty and effective protection of victims' rights within the implementation of restorative justice.